Analysis of the microbiota composition in the genital tract of infertile patients with chronic endometritis or endometrial polyps - Liang, Junhua; Li, Meng; Zhang, Lei; Yang, Yang; Jin, Xia; Zhang, Qiongqiong; Lv, Tao; Huang, Zhenyu; Liao, Qinping; Tong, Xiaowen (Frontiers in Cellular and Infection Microbiology, 2023)
Background The previous researches show that infertile patients have a higher incidence of endometritis and endometrial polyps, and the occurrence of these two diseases is related to changes in the microbiota of the genital tract. We aim to determine the composition and changing characteristics of the microbiota in the genital tract (especially the endometrium) of infertile patients with chronic endometritis or endometrial polyps, and find the correlation between it and the occurrence of diseases. Methods This is a prospective study. We collected genital tract biopsy samples from 134 asymptomatic infertile patients receiving assisted reproductive therapy before embryo transfer. Through pathological examination and 16S ribosomal RNA(16S rRNA) sequencing, we determined the distribution of chronic endometritis and endometrial polyps in these patients, as well as their distribution of reproductive tract microorganisms. Results Compared with the normal control group, the microbial group of reproductive tract in patients with chronic endometritis and endometrial polyps is changed, and there are significant species differences and relative abundance differences in the vagina, cervix and uterine cavity. Lactobacillus, the dominant flora of female genital tract, showed a change in abundance in patients with endometrial diseases. Endometrial microbiota composed of Staphylococcus, Gardnerella, Atopobium, Streptococcus, Peptostreptococcus, Chlamydia, Fusobacterium, Acinetobacter, etc. are related to chronic endometritis and endometrial polyps. Conclusion The results showed that, compared with the normal control group, the endometrial microbiota of infertile patients with chronic endometritis or endometrial polyps did have significant changes in the relative abundance distribution of species, suggesting that changes in local microecology may be an important factor in the occurrence of disease, or even adverse pregnancy outcomes. The further study of endometrial microecology may provide a new opportunity to further improve the diagnosis and treatment strategy of chronic endometritis.